Higher soil nitrous oxide production in landscape depressions linked to soil and hydrological legacy effects - Liu, Yujia; Siljanen, Henri M. P.; Kemmann, Björn; Ambus, Per; Paul, Dhiraj; Thiyagarasaiyar, Krishnapriya; Elberling, Bo; Wichern, Florian; Thorup-Kristensen, Kristian; Mueller, Carsten W.; Poultney, Daniel M. N. (Frontiers in Soil Science, 2025)
Background and aimsEastern Denmark’s agricultural landscapes feature numerous topographic depressions that are frequently flooded during late winter and spring. These poorly drained, carbon- and nitrogen-rich depression soils receive eroded material from adjacent slopes. Fertilization and water saturation create N2O emission hotspots. However, the potential legacy effects of these topographic locations on microbial communities involved in N2O production and reduction remain unclear. One approach to mitigating high denitrification rates (as a source of N2O) is to alter microbial pathways by adding nonhazardous levels of copper.MethodsWe conducted an incubation study using upland and depression soils from the same site, incorporating varying Cu levels (0, 130, and 260 mM) and water levels (60% and 90% water holding capacity).ResultsDepression soils emitted eight times more N2O than upland soils at 90% WHC. Cu addition did not reduce cumulative N2O emissions but delayed or lowered the flux peak. Depression soils exhibited 3,000- and 4,000-fold higher 16S rRNA and nosZ clade I abundances, respectively, compared to upland soils. Cu addition significantly decreased 16S rRNA abundance, eliminated AOB amoA in upland soils, and slightly reduced the tested gene abundances in depression soils. The nosZ gene community structure differed significantly between the two soils.ConclusionsOverall, our study suggests that erosional differentiation of soil properties, together with frequent waterlogging conditions, can result in distinct microbial communities, fostering legacy effects that lead to differences in N2O emissions between upland and depression soils. Adding Cu to these intensively managed soils is unlikely to be an effective strategy for mitigating N2O emission hotspots in arable fields.